Capsular Contraction Syndrome. Review. Part 1 - D. I. Ivanov; V. N. Nikitin (Oftalʹmologiâ, 2022)
The progressive increase of the number of phacoemulsification in the world leads to a proportional increase in the number of fibrous changes of the capsular bag in the postoperative period. Changes of the capsular bag occur even in simple cases. Structural changes in the lens capsule cause the development of contractional capsular syndrome. It occurs in up to 58.5 % of cases at various times after surgery. Clinical manifestations of contractional syndrome can be diverse: from an asymptomatic course to serious functional and anatomical disorders. The article provides general information about predisposing factors, conditions and causes of capsular syndrome. The paper considers the sequence of changes in the lens cells named epithelial-mesenchymal transformation. Transformation is the basis of the capsular syndrome pathogenesis. The article reveals the mechanisms of influence of the material and design of the IOL, size and shape of anterior rhexis on the development of the pathological process.